Rumo a uma clinica estrangeira ou por uma musicalidade intensiva - Cobo-Guevara, Paula (2022)
TOWARDS A FOREIGN CLINIC OR AN INTENSIVE MUSICALITY. It’s an experimentation that operates through, by and with various exercises – as devices of clinicalconceptual micro-elaborations which are approached from an aesthetic register of the thought of listening in practice. This clinical-writing – as transmission – draws upon a type of expressive and transductive conceptualization of certain questions that emerge singularly in the encounter of a depersonalized and singular psychoanalytical experience. From this experience, zones, trajectories, and regions of pneumatic and atmospheric intensification are presented – as an exercise in listening – without a point of departure or arrival, but rather a continuum. Zones that do not point to a unity, but to the heterogeneity that triggers the alliance of language and language as lalangue. That is to say, from a vibrational-vibratory register: musical. One moves through anarchic and foreign regionalities and topologies of the unconscious, performing and counter-performing modulations and movements that allows the virtual passing through the actual, of the perspectives of the drives traversed crossed. At times – the text as clinical thought – acquires degrees of depersonalized innocence necessary for a traversal that breaks through the subject and the self, entering the domains of the outside-of-itself. A foreign alliance outside the subject, as an ethical opening of agreed disposition, which is constructed to the extent that the intensities allow it. These are attempts at the vision and operation of a clinical ethics, as orientations of a thought and a know-how (savoirfare), where the minor, surface and slowness become the drive’s criteria of the landscapes and passages of The Life and A life